Pengembangan Media Interaktif Menggunakan Aplikasi Articulate Storyline Sebagai Media Pembelajaran IPA Di Sekolah Dasar - Hidayah, Nuriyatul; Nafitri, Siwi Es; Zaky, Fatihul; Ati MZ, A.F. Suryaning (Educational Consultant & Counseling Career (EC3) Mataram, 2023)
The lack of use of learning medai used by teachers in conducting learning and the lack of competence possessed by teachers so that they cannot untilize technology as learning media. The purpose of this study was to produse interactive learning media using the Articulate Storyline applocation as a medium for learning science in elementary schools. The research method used is R&D wite the ADDIE developmen model which consists of 5 stages, namely analysis, design, developmen, implementation and evaluation. The subjects of this study were 24 students who were going to try out media, media experts. After expert validation, the instrument validity and realiability were tested after going through limited trials in different primary schools. Interaktive media based on the Articulate Storyline can be said to be feasible with the results of testing the material by 81% which is categorized as very good and frome media experts as much as 78% which can be categorized well. Whereas frome the results of the responses to the questonnaire for student learning interest of 0,598, the statement was declared valid. And for reliability results as much as 0,925 is included in the very good category. From the tests that have been carried out, intractive media based on the Articulate Storyline is suitable to be used to assist teachers in delivering learning material.